Assessing the Influence of Patient Anxiety on the Efficacy of Endodontic Procedures - Shadab Ahmed; Priyanka Sharma; Anarasi Mahaprasad; Aditya Patel; Hitesh Chohan; Sabari Murugesan (Wolters Kluwer Medknow Publications, 2024)
Background: Patient anxiety is known to influence various aspects of dental procedures, including endodontic treatments. However, the extent of its impact on the efficacy of such procedures remains uncertain. Understanding this influence is crucial for improving patient outcomes and optimizing treatment protocols. Materials and Methods: A prospective cohort study was conducted involving 100 patients undergoing endodontic procedures. Patient anxiety levels were assessed using standardized anxiety scales before and after treatment. The efficacy of endodontic procedures was evaluated based on posttreatment pain scores, success rates of root canal treatments, and patient-reported satisfaction levels. Results: The mean pre-treatment anxiety score was 45.7 (SD = 9.2), while the mean posttreatment anxiety score reduced significantly to 32.4 (SD = 7.6), indicating a significant reduction in anxiety levels following endodontic procedures (P < 0.001). Posttreatment pain scores were lower in patients with reduced anxiety levels, with an average pain score of 2.1 (SD = 1.3) compared to 3.8 (SD = 1.6) in patients with persistently high-anxiety levels (P = 0.002). Additionally, the success rate of root canal treatments was higher in patients with lower anxiety levels (85%) than those with higher anxiety levels (65%) (P = 0.015). Overall patient satisfaction was also significantly higher in the low-anxiety group (P < 0.001). Conclusion: Patient anxiety significantly influences the efficacy of endodontic procedures, affecting posttreatment pain, success rates of root canal treatments, and patient satisfaction levels. Efforts to reduce patient anxiety before and during endodontic procedures may lead to improved treatment outcomes and higher patient satisfaction.